Today's Curricula: In Agricultural Journalism and Communications - James F. Evans; James G. Bolick (Journal of Applied Communications, 1982)
In 1956, William G. Mitchell found a serious lack of agreement among professionals about the kind of education needed for a career in agricultural journalism and communications.